The luminescence profile of carbon dots synthesized from α-cellulose under different acid hydrolysis conditions - Yann, Huey Ng; Suk, Fun Chin; Suh, Cem Pang; Sing, Muk Ng (Elsevier B.V., 2017)
This work reports the study on the luminescence properties portrayed by carbon dots synthesized under different acid hydrolysis conditions. Sulphuric acid was employed to dehydrate and carbonize α-cellulose as starting precursor. We revealed that the emissions of carbon dots were strongly dependent on the reaction condition during the synthesis, which include hydrolysis time and temperature. Initial mild acid hydrolysis at 4 °C and followed by incubation at room temperature was found favourable to the production of carbon dots emitting green fluorescence, whereas higher temperatures of 50 and 70 °C would produce carbon dots emitting blue fluorescence. At fixed temperature of 50 °C, prolonged synthesis time could shift the emission of carbon dots from green to blue. The green emission was recorded to have a peak at 500 nm when excited at 450 nm; whereas the highest intensity for the blue emission was recorded at 456 nm when excited at 357 nm. Both as-synthesized carbon dots showed excitation-independent emission. The quantum yields for the green and blue carbon dots were evaluated to be 6.4% and 4.0% respectively. The carbon dots emitting blue emission was of better photostability as compared to the carbon dots emitting green fluorescence. Both types of carbon dots synthesized in this study showed significant pH-dependent trend with higher intensity at lower pH condition.